1996
DOI: 10.1021/jp961871r
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Quartz Crystal Microbalance Study of Self-Assembly and Mass Transfer Processes of a Redox-Active Osmium Complex

Abstract: The adsorption process of the redox-active self-assembling molecule [Os(bpy) 2 (pydpy)Cl] + (bpy ) 2,2′-bipyridine and (pydpy) ) trans-1,2-bis(4-pyridyl)ethylene) onto a Pt electrode has been investigated in aqueous KClO 4 , KPF 6 , and KNO 3 electrolyte solutions using the quartz crystal microbalance in conjunction with cyclic voltammetry. In all the electrolyte solutions examined, the adsorption of the Os complex appears to be accompanied by water molecules, whose number is higher in KPF 6 solution (38-41) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…What is important, however, is that the resistance remained constant. Similar results have been reported for the self-assembly processes of aliphatic thiol molecules onto gold electrode surfaces [27], and of an osmium bipyridine derivative onto a platinum electrode [12]. Thus, these results indicate that the adsorbed dendrimer films, in a 0.10 M TBAP+AN solution, can be regarded as rigid, and that their film properties remain essentially constant with time.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…What is important, however, is that the resistance remained constant. Similar results have been reported for the self-assembly processes of aliphatic thiol molecules onto gold electrode surfaces [27], and of an osmium bipyridine derivative onto a platinum electrode [12]. Thus, these results indicate that the adsorbed dendrimer films, in a 0.10 M TBAP+AN solution, can be regarded as rigid, and that their film properties remain essentially constant with time.…”
Section: Resultssupporting
confidence: 86%
“…We have previously reported that the stirring does not affect the frequency stability, which was maintained to within AE1.7 Hz for 10 h after the establishment of a constant temperature (25.0 AE 0.1°C) [12]. Thus, we can safely neglect any effects of changes in the viscosity and density of the solution on the frequency.…”
Section: Apparatus and Proceduresmentioning
confidence: 95%
See 1 more Smart Citation
“…This excess of mass can be due to multilayers of Cyt c or, more likely, to the adsorption of water molecules and/or ions in solution. 57,58 The CVs illustrated in Figure 2B were obtained in the QCM cell just after the frequency steady state was reached, ca. 50 min of immersion in PBS solution containing Cyt c. Then, the apparatus was washed and filled with PBS solution and the CVs illustrated in Figure 2C were acquired.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In previously reported studies on the adsorption of Hpyt, 26 TNA, 25 and 1,4-dt 27 on gold, we found that the monolayers formed with these molecules present defects through which water molecules can penetrate. Also, Abrunã et al, 42 on the basis of a combination of QCM and cyclic voltammetry techniques, found that the formation of monolayers of an Os complex on Pt is accompanied by water molecules. Assuming that the mass difference between QCM and reductive desorption is due solely to water, the numbers of coadsorbed water molecules per molecule of adsorbate were calculated and are presented in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%